Proverbs and sayings in Sary (Yellow) Uighur language - Yeskeyeva, Мағрипа (Turkic Studies Journal, 2022)
Proverbs and sayings in the modern Turkic languages, which have their own way of formation, develop in close contact with the common Turkic paremiological system, which determines the directions of internal processes of disintegration of the common Turkic language system. The results of the study of a particular language contribute to finding solutions to problems in the Turkic language, complementing theoretical considerations, and identifying features of the common Turkic worldview. Proverbs and sayings preserved in the language of Yellow Uighurs in the assimilation process, along with the peculiarities of the ethnic worldview, contribute to revealing the features of the common Turkic worldview, clarifying the peculiarities of the development of the paremiological system of Turkic languages in general. The research study considers the meaning and features of the use of proverbs and sayings in the yellow Uighur language, which have a narrowed functional scope, in the context of the history, everyday life and traditions of the people, in the context of spiritual and cultural values. It is determined that changes in the situational use of a single paremiological meaning are also facilitated by the semantic field of dominant lexemes in proverbs and sayings. The ethno-cultural content of the Sary Uighur proverbs describing Tengrism, public and social relations, family and moral values is determined. Key lexemes in the structure of proverbs and sayings of Sary Uighur are compared with versions in the Kazakh language, structural, semantic and common features are distinguished. The Sary Uighur and Kazakh proverbs and sayings are compared, and the features of the content of paremia that characterize the common features of the Turkic peoples and the individual peculiarities of each nation are given. The research study used the materials of two field expeditions (07.2012; 09.2012) organized with the participation of the author to the settlement of the Yellow Uighurs in the Sunan region of the People’s Republic of China.